Targeting whole body metabolism and mitochondrial bioenergetics in the drug development for Alzheimer's disease - Steven N. Austad; Scott Ballinger; Thomas W. Buford; Christy S. Carter; Daniel L. Smith, Jr; Victor Darley-Usmar; Jianhua Zhang (Elsevier, 2022)
Aging is by far the most prominent risk factor for Alzheimer's disease (AD), and both aging and AD are associated with apparent metabolic alterations. As developing effective therapeutic interventions to treat AD is clearly in urgent need, the impact of modulating whole-body and intracellular metabolism in preclinical models and in human patients, on disease pathogenesis, have been explored. There is also an increasing awareness of differential risk and potential targeting strategies related to biological sex, microbiome, and circadian regulation. As a major part of intracellular metabolism, mitochondrial bioenergetics, mitochondrial quality-control mechanisms, and mitochondria-linked inflammatory responses have been considered for AD therapeutic interventions. This review summarizes and highlights these efforts.